Penerapan Konsep Inversion Of Control pada Sistem Informasi dengan Java Framework Google Guice - Novanto, Herdhian Cahya; Satoto, Kodrat Iman; Isnanto, R. Rizal (Transmisi, 2010)
Object-oriented concept is a set of methods for the analysis, design, and programming that enables software developers can build software that is reliable, easy to use, easy in maintenance, and well documented. The concept of Inversion of Control (IoC) is able to handle this by allowing class to organize existing objects. Java programming language is one of object-oriented programming language. Google Guice is a Java framework that embraces the concept of the IoC. This framework has several components, such as the binder, annotation, and modules. Information system application that is built to give the IoC concept modeling with Google Guice framework. While the  undertaken research steps is the analysis of the required classes, designing system with the Unified Modeling Language, implementation of the concept of IoC with Google Guice framewrok, and testing of desktop applications. From the testing that has been done, it can be concluded that,  firtsly, the design produces modeling program with programming concepts IoC, secondly Google Guice framework configuration placing objects in another class, thirdly Google Guice can help software developers in doing the development, modification, testing, and facilitate the reuse , the fourth Google Guice framework can reduce the interference in class user interface. Keyword :   Inversion of Control, framework, Google Guice, Java, object oriented.